Stability of Epidoxorubicin Hydrochloride in Aqueous Solutions: Experimental and Theoretical Studies - Agnieszka Sobczak; Monika A. Lesniewska-Kowiel; Izabela Muszalska; Artur Firlej; Judyta Cielecka-Piontek; Szymon Tomczak; Bolesław Barszcz; Irena Oszczapowicz; Anna Jelińska (Journal of Chemistry)
The first-order degradation kinetics of epidoxorubicin were investigated as a function of pH, temperature, and buffers concentrations. The degradation was followed by HPLC. Buffer catalysis was observed in acetate and phosphate buffers. The pH-rate profiles were obtained at 333, 343, 353, and 363 K. The pH-rate expression was kpH=k1×aH+×f1+k2×f1+k3×f2+(k4×f2+k5×f3)×aOH-, where k1, k4, and k5 are the second-order rate constants (mol−1 L s−1) for hydrogen ion activity and for hydroxyl ion activity, respectively, and k2 and k3 are the first-order constants (s−1) for spontaneous reaction under the influence of water. Epidoxorubicin demonstrates the greatest stability in the pH range 3–5. The electrostatic molecular potential orbitals HOMO-LUMO were also defined in order to determine the cause of the reactivity of particular epidoxorubicin molecule domains in solutions with various pH values.